Treatment of childhood acute lymphoblastic leukemia with delayed first intrathecal therapy and omission of prophylactic cranial irradiation: Results of the TPOG‐ALL‐2002 study. Issue 23 (10th October 2018) - Yeh, Ting‐Chi; Liang, Der‐Cherng; Hou, Jen‐Yin; Jaing, Tang‐Her; Lin, Dong‐Tsamn; Yang, Chao‐Ping; Peng, Ching‐Tien; Hung, Iou‐Jih; Lin, Kai‐Hsin; Hsiao, Chih‐Cheng; Jou, Shiann‐Tarng; Chiou, Shyh‐Shin; et al.
Abstract : Background: To eliminate cranial irradiation (CrRT)–related sequelae and to minimize the adverse impact of traumatic lumbar puncture (TLP) with blasts, the Taiwan Pediatric Oncology Group (TPOG) introduced a modified central nervous system (CNS)–directed regimen characterized by delayed triple intrathecal therapy (TIT) and the omission of CrRT for all children with newly diagnosed acute lymphoblastic leukemia (ALL). Methods: This study compared the treatment outcomes of patients overall and patients with a non–CNS‐1 status (CNS‐2, CNS‐3, or TLP with blasts) in 2 treatment eras, one before and another after the revision of the TPOG‐ALL‐2002 protocol by the introduction of the modification (era 1 [2002‐2008] with CrRT and era 2 [2009‐2012] with delayed first TIT and no CrRT). Results: There were no statistically significant differences in major outcomes between the 903 patients treated in era 1 and the 444 patients treated in era 2: the 5‐year event‐free survival (EFS) rates were 75.7% ± 1.4% and 72.1% ± 2.4%, respectively ( P = .260), and the cumulative risks of isolated CNS relapse were 4.0% ± 0.7% and 4.1% ± 1.0%, respectively ( P = .960). There were also no differences between non–CNS‐1 patients treated in era 1 (n = 76) and era 2 (n =28): the 5‐year EFS rates were 52.3% ± 5.8% and 62.9% ± 9.4%, respectively ( P = .199), and the cumulative risks of isolated CNS relapse were 6.3% ± 3.1% and 3.6% ± 3.5%, respectively ( P = .639). Notably, TLP with blasts was completely eliminated after the first TIT was delayed in era 2. Conclusions: The delay of the first TIT until the clearance of circulating blasts and the total omission of CrRT did not compromise survival or CNS control in patients with childhood ALL, including those with a non–CNS‐1 status. Abstract : In this study, the delay of first triple intrathecal therapy until the clearance of circulating lymphoblasts and the total omission of cranial irradiation do not compromise survival or central nervous system control in childhood acute lymphoblastic leukemia, even when analyses are limited to patients with a non‐CNS‐1 status.